2019
DOI: 10.1159/000495886
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Features of Fabry Disease in Hemodialysis Patients: Russian Nationwide Fabry Dialysis Screening Program

Abstract: Aim: To evaluate the prevalence and clinical features of Fabry disease in patients with end-stage renal disease (ESRD) undergoing chronic hemodialysis. Methods: α-Galactosidase A activity was measured in the dried blood spots by tandem mass spectrometry in 5,572 dialysis patients (63.7% males). Diagnosis of Fabry disease was confirmed by sequencing of the GLA gene and by evaluating the globotriaosylsphingosine level in the dried blood spots. Results: Fabry disease was diagnosed in 20 (0.36%) patients at the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
0
18
1
8
Order By: Relevance
“…Early symptoms of FD, that is, neuropathic pain (pain in hands and/or feet characterised by exacerbations that are provoked by fever, exercise or heat), angiokeratoma (clustered angiomas in characteristic areas including bathing trunk area, lips and umbilicus) (figure 1), hypohidrosis/anhidrosis and gastrointestinal disorders, are usually present from childhood or adolescence, while progressive nephropathy, left ventricular hypertrophy (figure 2) and stroke/transient ischaemic attacks develop by the second to fourth decades of life (earlier in males than in females) 1. Undiagnosed patients with FD can be detected by screening in at-risk populations, such as patients with end-stage renal disease, unexplained myocardial hypertrophy or early stroke (at the age of 18 to 55 years) 2…”
mentioning
confidence: 99%
“…Early symptoms of FD, that is, neuropathic pain (pain in hands and/or feet characterised by exacerbations that are provoked by fever, exercise or heat), angiokeratoma (clustered angiomas in characteristic areas including bathing trunk area, lips and umbilicus) (figure 1), hypohidrosis/anhidrosis and gastrointestinal disorders, are usually present from childhood or adolescence, while progressive nephropathy, left ventricular hypertrophy (figure 2) and stroke/transient ischaemic attacks develop by the second to fourth decades of life (earlier in males than in females) 1. Undiagnosed patients with FD can be detected by screening in at-risk populations, such as patients with end-stage renal disease, unexplained myocardial hypertrophy or early stroke (at the age of 18 to 55 years) 2…”
mentioning
confidence: 99%
“…Numerous studies have examined the prevalence of Fabry disease in haemodialysis (HD) populations worldwide, with estimated prevalence ranging from 0.12% [28,29] to 0.36% [30]. Fabry screening studies of Japanese HD populations [17,[31][32][33][34][35] estimate prevalence at 0.3 to 0.7% [32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Fabry screening studies of Japanese HD populations [17,[31][32][33][34][35] estimate prevalence at 0.3 to 0.7% [32,34,35]. Prevalence studies of European HD populations estimate Fabry prevalence at between 0.15 and 0.36% [30,[36][37][38]. A Brazilian study estimated the prevalence of Fabry disease in haemodialysis patients to be 0.12% [28].…”
Section: Introductionmentioning
confidence: 99%
“…As the clinical diagnosis of FD is challenging; therefore, screening of subjects with clinical suspicion of the disease is important. [13][14][15][16][17][18] Early detection and initiation of enzyme replacement therapy (ERT) may slow the progression of the disease. [19][20][21][22] Wide-scale newborn screening has been implemented for FD in many countries.…”
mentioning
confidence: 99%
“…A similar approach was adopted in previous studies, which reported a prevalence of 0.2-1.7% of FD in patients with chronic kidney disease depending on the population screened and the method of screening. 1,[10][11][12][13][14][15][16][17][18] Linthorst et al, 13 conducted a systematic review of FD screening of high-risk populations. The authors showed that the average prevalence of FD among hemodialysis patients was 0.33% in males and 0.10% in females.…”
mentioning
confidence: 99%